HUBUNGAN ANTARA STATUS GIZI DAN POLA ASUH DENGAN TINGKAT PERKEMBANGAN BALITA USIA 4-5 TAHUN DI KECAMATAN SUKOREJO KABUPATEN KENDAL - Ardian Candra Mustikaningrum; Siti Munawaroh (LPPM STIKES Muhammadiyah Kendal, 2021)
The first five years of life time is a very sensitive time to the environment. Lack of nurition and unproper treatment can influence the children development. The biggest number of Red Underline (BGM) children under five and child development disturb in Sukorejowich number 1,08%. So the problem that want to be discused is the correlation between nutrition status and rear pattern with the development level on children under five the age 4-5 years old in Sukorejo. The type of this research is explanatory research with survey method and cross sectional approach. The population of the research is children under five in the age 4-5 years old in Sukorejo wich number 153 children. The sample of the research are 60 children under five in the age of 4-5 years old. Sample was selected by purposive sampling. Instrument that was used are Pra Screening Development Quetioner, Nutrition rear pattern quetioner, a strirrup scale and microtoice. The obtained data was analyzed by chi-square.. Result of the research show that are 31,7% children under five with good nutrition status , middle nutrition status 38,3% and low nutrition status 40 %. Where as children with good nutrition treatment 28,3%, middle nutrition treatment 40% and low nutrition treatment 32%. Discription of the children under five development level according to the age is 30%, doubt development 33,3 % and the level with deviation is 36,7%. From staistic proper test resulted p= 0,001 and CC=0,728 for nutrition status of children under five with development level and p= 0,003 and CC = 0,463 for rear pattern with development level. Conclusion of the research is there is a correlation between nutrition status with the development level of children under five in the age 4-5 years old in Sukorejo. The suggestion for the instance of health organizer is should have a relationship with the official of planned family welfare to distribute the form of BKB so that the early stimulation can be optimal. Mothers who have children under five should be routine in posyand